Citotoxidade de cimentos resinosos sobre célular obtidas da polpa de dentes humanos (HDPCs) e odontoblastóides (MDPC-23) - Pontes, Elaine Cristina Voltolini [UNESP] (2014)
The aim of this study was to evaluate the cytotoxicity of luting cements on cultured MDPC-23 odontoblast-like cells and human dental pulp cells (HDPCs). The following groups were formed: G1 - control (no treatment), G2 - Rely X Luting 2, G3 - Rely X U200; G4 - Rely X ARC. Standard round specimens prepared with resin cements were immersed in 1 ml of culture medium (DMEM) for 24 hours to obtain the extract (DMEM + components released from the cement). After applying the extracts to the cells for 24 hours, the viability (MTT assay) and type of cell death (Annexin/PI) as well as cell morphology (SEM) were evaluated. The data obtained was submitted to Kruskal-Wallis statistical analysis complemented by Mann-Whitney test (α=5%). The chemical analysis of the extracts was performed by high performance liquid chromatography (HPLC). In G2, G3 and G4, there was a reduction of 95.8 %, 31.5 % and 22.7 % in the MDPC-23 cells viability, respectively. A reduction of 89.4 % for G2, as well as an increase of 11.3 % and 29% for G3 and G4 was observed for the HDPCs, respectively. Significant reduction of MDPC-23 viability occurred for G2 and G3 compared to G1. However, for HDPCs this reduction was only observed in G2 (p<0.05). For both cell cultures used in this study, there was 10 % of cell death by necrosis only in G2, in which the pH of the extract was acid. In G3, where a small amount of TEGDMA was detected in the extracts, there was reduced cell death by necrosis and a discrete morphological alteration in cells. No cellular damage occurred in G4. In general, the MDPC-23 cells are more sensitive than HDPCs against the toxicity of resin cement components. It was found that only the Rely X Luting cement caused intense cytotoxic effect for both pulp cell cultures used in this study. Rely X U200 showed mild cytotoxicity, whereas the cement Rely X ARC was not toxic to the pulp cells.